The legal guide for museum professionals - Courtney, Julia Hollett (Rowman and Littlefield, 2015)
From intellectual property law to navigating the hazards of social media, de-accessioning concerns to governance law, copyright, intellectual property law, and rights and reproduction questions to issues of public trust, The Legal Guide for Museum Professionals provides answers and action steps for mid to small-sized museums of all disciplines.